Apoptosis Signal-regulating Kinase 1 (ASK1)-p38 Pathway-dependent Cytoplasmic Translocation of the Orphan Nuclear Receptor NR4A2 Is Required for Oxidative Stress-induced Necrosis - Watanabe, Takeshi (J Biol Chem, 2015)
p38 mitogen-activated protein kinases (MAPKs) play important roles in various cellular stress responses, including cell death, which is roughly categorized into apoptosis and necrosis. Although p38 signaling has been extensively studied, the molecular mechanisms of p38-mediated cell death are unclear. ASK1 is a stress-responsive MAP3K that acts as an upstream kinase of p38 and is activated by various stresses, such as oxidative stress. Here, we show that NR4A2, a member of the NR4A nuclear receptor family, acts as a necrosis promoter downstream of ASK1-p38 pathway during oxidative stress. Although NR4A2 is well known as a nucleus-localized transcription factor, we found that it is translocated into the cytosol after phosphorylation by p38. Because the phosphorylation site mutants of NR4A2 cannot rescue the cell death-promoting activity, ASK1-p38 pathway-dependent phosphorylation and subsequent cytoplasmic translocation of NR4A2 may be required for oxidative stress-induced cell death. In addition, NR4A2-mediated cell death does not depend on caspases and receptor-interacting protein 1 (RIP1)-RIP3 complex, suggesting that NR4A2 promotes an RIP kinase-independent necrotic type of cell death. Our findings may enable a more precise understanding of molecular mechanisms that regulate oxidative stress-induced and p38-mediated necrosis.